A Near-Wall Methodology for Large-Eddy Simulation Based on Dynamic Hybrid RANS-LES - Michael Tullis; D. Keith Walters (Entropy)
Attempts to mitigate the computational cost of fully resolved large-eddy simulation (LES) in the near-wall region include both the hybrid Reynolds-averaged Navier–Stokes/LES (HRL) and wall-modeled LES (WMLES) approaches. This paper presents an LES wall treatment method that combines key attributes of the two, in which the boundary layer mesh is sized in the streamwise and spanwise directions comparable to WMLES, and the wall-normal mesh is comparable to a RANS simulation without wall functions. A mixing length model is used to prescribe an eddy viscosity in the near-wall region, with the mixing length scale limited based on local mesh size. The RANS and LES regions are smoothly blended using the dynamic hybrid RANS-LES (DHRL) framework. The results are presented for the turbulent channel flow at two Reynolds numbers, and comparison to the DNS results shows that the mean and fluctuating quantities are reasonably well predicted with no apparent log-layer mismatch. A detailed near-wall meshing strategy for the proposed method is presented, and estimates indicate that it can be implemented with approximately twice the number of grid points as traditional WMLES, while avoiding the difficulties associated with analytical or numerical wall functions and modified wall boundary conditions.